2013
DOI: 10.1007/s11764-013-0271-0
|View full text |Cite
|
Sign up to set email alerts
|

Family physician preferences and knowledge gaps regarding the care of adolescent and young adult survivors of childhood cancer

Abstract: Adult and adolescent survivors of childhood cancer who receive their follow-up care from a family physician must be empowered to choose a physician who is comfortable with caring for survivors. Further, the survivor must ensure that their physician has access to a treatment summary as well as to patient-specific recommendations for surveillance for late effects of cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
158
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 24 publications
10
158
0
Order By: Relevance
“…56,58,60,62,69,70 PCPs suggested improving post-treatment follow-up through a shared data management system, 53 such as the broad integration of electronic medical records and standard communication procedures between PCPs and specialists. 65,70 Provision of patient-specific standard guidelines notated by oncologists 40,44,48,59,69 or meetings aimed at sharing information and defining roles 38 were also endorsed. Electronic communication and mail were valued, 40,58,65,69 but not to the exclusion of personal interaction with specialists, which was preferred.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
See 3 more Smart Citations
“…56,58,60,62,69,70 PCPs suggested improving post-treatment follow-up through a shared data management system, 53 such as the broad integration of electronic medical records and standard communication procedures between PCPs and specialists. 65,70 Provision of patient-specific standard guidelines notated by oncologists 40,44,48,59,69 or meetings aimed at sharing information and defining roles 38 were also endorsed. Electronic communication and mail were valued, 40,58,65,69 but not to the exclusion of personal interaction with specialists, which was preferred.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
“…69 For the management of paediatric cancer survivors, one study reported that 30-40 % of PCPs had participated in a conversation with a colleague about survivorship care, participated in medical education activities, or read one or more survivorship articles, and approximately 20 % had experienced formal training, possibly as distant as during their undergraduate studies. 59 lack of time and workload pressure, 49,52,64,71,72 lack of remuneration and inadequate funding, 49,52,72 lack of patient trust, 44,64 inadequate resources including cancer-specific guidelines and opportunities for mental health or multi-disciplinary referrals 40,47,52,60,69 and increased medicolegal risk. 72 Qualitative and quantitative results are summarized in Table 3.…”
Section: Information Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many feel unprepared to take on postcancer care independently. [40][41][42] In a hybrid model, PCPs share care with a cancer center team that provides guidance on cancer-related issues. No studies compare effectiveness of these models.…”
mentioning
confidence: 99%